2016
DOI: 10.1007/s00011-016-0943-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of baicalin on allergic response in ovalbumin-induced allergic rhinitis guinea pigs and lipopolysaccharide-stimulated human mast cells

Abstract: These results suggest that baicalin can effectively prevent allergic response in OVA-induced allergic rhinitis guinea pigs and inhibit inflammatory response via blocking JAK2-STAT5 and NF-κB signaling pathways in LPS-stimulated human mast cells. Considered together,the results show that baicalin may be a useful drug in the treatment of allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…In other words, one possible explanation for the anti-inflammatory effects of artemisinin might be the inhibition of MAPK pathways, which reduced the levels of inflammatory mediators. It is also well-known that MAPKs play important roles in the activation of NF-κB, which regulates a wide variety of genes involved in the allergy process [ 24 , 25 ]. Our study illustrated that artemisinin inhibited the activation of ERK, while the effect of artemisinin on the NF-κB pathway should be validated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, one possible explanation for the anti-inflammatory effects of artemisinin might be the inhibition of MAPK pathways, which reduced the levels of inflammatory mediators. It is also well-known that MAPKs play important roles in the activation of NF-κB, which regulates a wide variety of genes involved in the allergy process [ 24 , 25 ]. Our study illustrated that artemisinin inhibited the activation of ERK, while the effect of artemisinin on the NF-κB pathway should be validated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…(BC) (7-D-glucuronic acid-5,6dihydroxyflavone) is a flavonoid extracted from the dried roots of Scutellaria baicalensis Georgi which has been clinically utilized as the traditional medicines and the nutritional supplements [9]. BC is known for its several pharmacological actions, including antiinflammatory and anti-allergic properties [10,11]. Studies using several cell lines and animal models have reported BC or herbal extracts rich in BC to possess anti-proliferative or anti-tumor effects [12][13][14].…”
Section: Baicalinmentioning
confidence: 99%
“…Allergic rhinitis (AR) is a type of chronic inflammation in the respiratory tract [1]. It is a very common disease of nasal mucosa, triggered by the interaction of specific immunoglobulin E (IgE) and ubiquitous environmental proteins in sensitized patients [2]. The main symptoms of AR are sneezing, rhinorrhea, itching and nasal congestion; these symptoms are usually accompanied by other related symptoms such as nasal mucosa swelling [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of natural products for treating AR has been increasing worldwide; many prior trials have evaluated the effectiveness of herbal medicines for AR [10]. Baicalin, a flavonoid compound isolated from Scutellaria baicalensis Georgi, has been shown to have multiple pharmacological activities, including anti-allergic, anti-inflammatory and antioxidant effects [2]. Based on its anti-allergic and anti-inflammatory activity, baicalin is widely used to treat various allergic and inflammatory diseases, including asthma, atopic dermatitis and AR [11].…”
Section: Introductionmentioning
confidence: 99%